REPRECUSIONS OF THE INTRODUCTION AND CHANGE OF THE VALUE ADDED TAX RATE ON THE DYNAMICS OF THE BUDGET DEFICIT - Janković, Gordan (Economic Outlook, 2025)
This paper analyzes the impact of value added tax (VAT) on the volume of the budget deficit. As part of the research, we focus on the mechanisms through which the value-added tax affects state, i.e. public revenues, consumption and economic activity. Through a quantitative analysis of available data and a review of relevant theoretical frameworks, we determine how changes in the value added tax rate can affect the budget deficit, especially in the context of fiscal stability. The results show that a properly set value added tax can contribute to reducing the budget deficit, while inadequate fiscal policies can lead to an increase in the deficit.
Keywords: Public revenues, fiscal policy, budget deficit, indirect taxes, VAT.